Práticas pedagógicas: aproximações dos princípios da educação do campo na Escola Vovó Vina, em Santa Rita-PB - Bizerra, Ladjane Fidelis Felinto (2020)
This research, entitled Pedagogical Practices: approximations of the principles of Rural Education at Escola Vovó Vina, in Santa Rita - PB, is part of the Master's course in Education, in the Popular Education Research Line, linked to the Graduate Program in Education , from the Federal University of Paraíba. The object of study of this research “pedagogical practices”, is inserted in the school context, in which it was perceived contradiction experienced by the researched school, between different education projects. In this sense, we express our concern through reflection on the context of struggles to guarantee legitimate rights, we seek to understand how to materialize the educational action proposed in the official documents, based on the perception of the principles that guide the practices of the school under study. ? For this, we seek to analyze in the pedagogical practices of the Municipal School Vovó Vina, the approximations with the principles of Rural Education. This research will go through the following specific objectives: to characterize the pedagogical proposals existing in the school; identify pedagogical practices that are close to the principles of Rural Education; to analyze the educational processes that bring the school closer to the principles of Rural Education. The research has as an epistemological option the dialectical materialistic historical approach, highlighting the theoretical category contradiction and, as empirical categories, work and territory. This is a qualitative field research. In the data collection process we used documentary research, participant observation and semi-structured interviews with 3 (three) teachers, 1 (one) supervisor and 1 (one) manager of the school. As a data analysis technique, we used Content Analysis, in Bardin (2011). As a result of this research, elements that point to the insertion of Rural Education in the pedagogical practices of the school in which the research was developed are visualized, such as: Interdisciplinarity, Sustainable Development, Dialogue, Human Formation, Collective Practice, Valorization of work and reality, Autonomy and collaboration. We consider that even with the presence of these pedagogical principles in the practices of the school studied, there is an absence of a fundamental element, which is the criticality in this process.